Impact of Cyberbullying on Mental Health and Growing Female Rape: Field Study on a Sample of Female Victims of Cyberbullying on Facebook - Ahmedi, Khaoula (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2022)
The current study aims to identify the impact of cyberbullying on mental health and the growing phenomenon of rape, to that end, we used the descriptive analytical approach because it's the best fit for the study problem, and by applying the mental health measure and a form with an open question about being raped or not on a sample of (60) females, we got the following results: . Cyberbullying affects mental health. . Cyberbullying affects the growing phenomenon of rape. Based on the results obtained, it is clear that the stakeholders need to move to take care of the phenomenon of cyberbullying to reduce it for the safety and security of the individual and society.
Keywords: التنمر الإلكتروني -- التنمر الجنسي -- الصحة النفسية -- المشاكل النفسية -- ظاهرة الاغتصاب